2020
DOI: 10.3390/min10020089
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Spectroscopic Study of Heavy-Metal-Contaminated Loess Soils in Tongguan Gold Area, Central China

Abstract: Loess soil is a kind of widespread soil type in northwest China. Human engineering activities such as mining have caused numerous problems related to heavy metal pollution in soils, which threaten people’s health. The band formation mechanism of the near-infrared (NIR) spectral features in loess soils forms the theoretical basis for the study of the soil environment by hyperspectral remote sensing. Some NIR features of loess soils will shift because of the variations of the soil composition and microstructure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Moreover, the presence of moisture in these surficial sediments of agricultural areas overrides the clay absorption feature in their spectral signature, making the irrigated agricultural fields more prominent in band ratio analysis than the immediately adjacent brick making areas (visible in Figure 13). The band ratio values in this region may also be affected by un-examined factors such as absorption of heavy-metals from nearby industrial and developed areas, which has been shown to cause changes in the absorption of NIR and SWIR wavelengths [25].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the presence of moisture in these surficial sediments of agricultural areas overrides the clay absorption feature in their spectral signature, making the irrigated agricultural fields more prominent in band ratio analysis than the immediately adjacent brick making areas (visible in Figure 13). The band ratio values in this region may also be affected by un-examined factors such as absorption of heavy-metals from nearby industrial and developed areas, which has been shown to cause changes in the absorption of NIR and SWIR wavelengths [25].…”
Section: Discussionmentioning
confidence: 99%
“…59 However, the positions of characteristic NIR bands are determined by the composition of the soil, and spectrometry can locate the spectral wavelength with high accuracy 60 ; therefore, a prediction model based on absorption band locations and heavy metals contents according to the mineral properties of loessal soils may be able to solve this problem. 3 Many mineralogical studies on the loess soil covering northwest China have shown that illite is the dominant clay mineral. 61 This study indicated an abundance of quartz, albite, and pyrite, with strong XRD peaks.…”
Section: Discussionmentioning
confidence: 99%
“…The interlayer domain is typically filled with K but can also capture Ca, Mg, Pb, Cd, Mn, Cu cations (Figure 1). 3 Therefore, the intercalation of cations gives illite minerals the ability to adsorb heavy metal cations. 7 The detection of heavy metals in soil mainly relies on traditional chemical analysis methods, such as atomic fluorescence spectroscopy, atomic absorption spectroscopy, and inductively coupled plasma mass spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations